A muse of fire - MacNeil, Robert (Sydney, NSW. : BBC Education & Training, 1986)
Tells the story of the English language in the days of Shakespeare and the King James' Bible
Keywords: Shakespeare, William, 1564 -- 1616 -- Language; English language -- Early modern, 1500 -- 1700; English language -- Foreign words and phrases